Penerapan Evidence Based Nursing Tepid Sponge Bath dalam Menurunkan Suhu Tubuh Anak Demam - Rafael, Stefanus Evan; Yusuf, Ah; Nihayati, Hanik Endang; Abiyoga, Aries (Journal of Telenursing (JOTING), 2023)
This study aims to analyze tepid sponge baths' effect in reducing hyperthermic children's body temperature. The research method used by Quasy is an experimental pre-test and post-test design. This study's results show a significant change in pre-measurements in respondents with hyperthermic body temperature. The criteria for achieving body temperature within normal limits with the tepid sponge bath intervention for 10-15 minutes, the post-test results show a decrease in the average body temperature of respondents from 38.5℃ to 36.5℃ in 10 respondents, the results criteria were achieved. In conclusion, providing tepid sponge bath therapy effectively reduces body temperature in children who experience problems treating hyperthermia. Keywords: Hyperthermia, Childhood Concept, Increased Body Temperature, Tepid Sponge Bath